Design & Estimation of Solar Based ATM Counter - Jana, Roni; Ghosh, Somnath; Paul, Anjalika; Saha, Amrita; Roy, Amartya (International Journal of Computer Sciences and Engineering, 2025)
This paper demonstrates a theoretical cost calculation for a particular Automated Teller Machine (ATM) counter which will operate through solar energy. Basically the paper is deal with two situations. First we represent the monthly cost when the ATM counter is not operate through solar energy and the next situation is that we calculate the cost when it is operate through solar energy. In this paper, we are going to discuss how we can reduce the cost for the particular ATM counter through solar energy. At last, we show the payback time for the operation process through solar energy. This will be a good option for the future and the overall result will provide an efficient system.